Action spectroscopy of a protonated peptide in the ultraviolet range1. Issue 39 (21st October 2015) - Canon, Francis; Milosavljević, Aleksandar R.; Nahon, Laurent; Giuliani, Alexandre
<x xml:space="preserve">Abstract</x> Action spectroscopy of substance P, a model undecapeptide, has been probed from 5.2 eV to 20 eV.